ASPEK NILAI KEARIFAN DALAM PERSPEKTIF EKOLOGI NOVEL "MAGENING" KARYA WAYAN JENGKI SUNARTA - Aryani, Ni Wayan (Widyadari : Jurnal Pendidikan, 2019)
Novel literary works that are present in the midst of society is one form of culture that presents about the natural state of the environment is quite good. With a 26-story storytelling, the author reveals a lot of the natural environment, it's just that his speech lacks poetic language, meaning that the style of language used is still ordinary, not much use of cliché languages ??like those read like in short stories and novels at times previous. Quite a lot of authors pour the values ??of local wisdom which of course there is a hidden education of people's lives. The nuance that is highlighted is the state of magening where people like to eat or drink wine. Thus the value of education is still relatively lacking. However, at least this author's work can be used as reference material for the development of research in the Anyar Bali literature as follows. Adding a wealth of reading material in the field of literature studies in the archipelago, especially in the form of literary novels, as a foundation for the community to imitate good behavior on the social values ??implicit in the Magening novel, opening opportunities for literary and literary researchers to continue this analysis so that it will have an impact positive for the addition of literary treasures.